Bioartificial liver. - Reis, J (Acta Médica Portuguesa, 1998)
Fulminant hepatic failure remains without satisfactory medical treatment and with a mortality rate of nearly 90%. Liver transplantation is the only chance to save these patients. However, there is a shortage of donors and many patients die before transplantation. It is thus necessary to develop a liver support system to help maintain patients alive, neurologically intact until an organ becomes available for transplantation, or ideally until hepatic regeneration. Early systems had only a depuration function, but now these systems include hepatocytes to replace most hepatic functions.